Sagot :
bonjour,
A) ( 6 x+3)(4 x-5) + (3 x+1)(6 x+3)
= ( 6 x + 3 ) ( 4 x - 5 + 3 x + 1 )
= ( 6 x + 3 ) ( 7 x - 4 )
B ) (3 x+5)(3-2 x)-(3 x+5)(2+5 x)
= ( 3 x + 5 ) ( 3 - 2 x - 2 - 5 x )
= ( 3 x + 5 ) ( - 7 x + 1 )
C ) ( 4 x+3)(3-2 x)-(4 x+3)(5-4 x)
= ( 4 x + 3 ) ( 3 - 2 x - 5 + 4 x )
= ( 4 x + 3 ) ( 2 x - 2 )
= 2 ( 4 x + 3 ) ( x - 1 )
D ) (4 x-5)(2-x)+(4 x-5)²
= ( 4 x - 5 ) ( 2 - x + 4 x - 5 )
= ( 4 x - 5 ) ( 3 x - 3 )
= 3 ( 4 x - 5 ) ( x - 1 )
E) (3 x+4)² - (3 x+4)(5 x+6)
= ( 3 x + 4 ) ( 3 x + 4 - 5 x - 6 )
= ( 3 x + 4 ) ( - 2 x - 2 )
= 2 ( 3 x + 4 ) ( - x - 1 )
le second est la même chose donc regarde ce que j'ai fait et inspire t'en